2018
DOI: 10.1002/hpm.2509
|View full text |Cite
|
Sign up to set email alerts
|

Drivers behind widespread informal payments in the Romanian public health care system: From tolerance to corruption to socio‐economic and spatial patterns

Abstract: In order to explain informal payments in public health care services in Romania, this paper evaluates the relationship between extra payments or valuable gifts (apart from official fees) and the level of tolerance to corruption, as well as the socio-economic and spatial patterns across those individuals offering informal payments. To evaluate this, a survey undertaken in 2013 is reported. Using logistic regression analysis, the findings are that patients with a high tolerance to corruption, high socio-economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
2
27
0
1
Order By: Relevance
“…This confirms the research hypothesis H4. Moreover, these research findings appear consistent with those studies that show that informal payments can deter access to health services for people with less ability to pay (Allin, Davaki & Mossialos, 2006;Azfar & Gurgur, 2008;Belli Gotsadze & Shahriari, 2004;Falkingham, 2004;Lewis, 2000;Rose, 2006;Habibov & Cheung, 2017;Horodnic, Mazilu & Oprea, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This confirms the research hypothesis H4. Moreover, these research findings appear consistent with those studies that show that informal payments can deter access to health services for people with less ability to pay (Allin, Davaki & Mossialos, 2006;Azfar & Gurgur, 2008;Belli Gotsadze & Shahriari, 2004;Falkingham, 2004;Lewis, 2000;Rose, 2006;Habibov & Cheung, 2017;Horodnic, Mazilu & Oprea, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, there are only a handful of studies that have systematically analysed the relation between corruption and these different performance dimensions. Some studies have focused on the effect of petty corruption on the equity of access or on the quality of the health service delivery (Azfar and Gurgur, 2008;Belli Gotsadze & Shahriari, 2004;Falkingham, 2004;Lewis, 2002;Maestad & Mwisongo, 2011;Balabanova & McKee, 2002;McPake, Asiimwe, Mwesigye, Ofumbi, Ortenblad, StreeflandP &Turinde, 1999;Gaal & McKee, 2005;Habibov & Cheung, 2017;Horodnic, Mazilu & Oprea, 2018). But to date, no study has jointly considered the relation of corruption with the above-mentioned performance dimensions, nor has any study conducted a sub-national level analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the equity perspective, IPs can reduce patients' access to essential treatments because only people with high financial strength can pay for treatment services. 11 The findings of this study showed that most patients in all three attitude groups opposed cash IPs and gifts to medical staff as a compensation for their low salary. The findings of some studies in Central and Eastern Europe reported that most people agreed with cash IPs and gifts to medical staff for compensating the health care -697 providers for their low salaries, which findings are inconsistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 66%